Students' mathematical communication skills viewed from mathematical resilience in probing-prompting learning with performance assessment - Cielo Dewi Cahyani; Walid Walid; Bambang Eko Susilo (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
By evaluating students’ performance in their mathematical communication skills and characterizing those skills in terms of their mathematical resilience, this study seeks to determine the efficacy of probing-prompting learning. A mixed method by using a sequential explanatory research design is employed. The study was conducted in two phases: first, quantitative data was collected and analyzed, then based on the findings of the quantitative data, qualitative data was collected and analyzed. The results of the research show that (1) the probing-prompting model with performance assessment is effective to improve students' mathematical communication skills and mathematical resilience and (2) based on the analysis of mathematical communication skills regarding students' mathematical resilience, it shows that students who have low stage of mathematical resilience are only able to express one indicator of mathematical communication skills, while students who have moderate and high stages of mathematical resilience are able to express five indicators of mathematical communication ability. The conclusion is probing-prompting learning with performance assessment can be used to improve students' mathematical communication skills and based on students’ mathematical resilience, students also have different levels of mathematical communication skills.